The Potential of Moringa Leaf Nanoparticles (Moringa oleifera) on the Expression of TNFα, IL10, and HSP 27 in Oral Cavity Cancer - Theresia Indah Budhy; Deddy Adam; Zulikran Moh Rizki Azis; Vania Syahputri; M Gandul Atik Yuliani; Muhammad Febriano Sugiarso Suwarto; Fery Setiawan (Journal of Multidisciplinary Applied Natural Science, 2024)
Oral cancer is currently the sixth leading malignancy in the world, with over 330,000 cases resulting in death. Several cytokines and proteins protect the survival of cancer cells, such as TNF-α, HSP27, and IL-10. Moringa oleifera is an herbal medicine with anti-cancer properties. Nanoparticles of M. oleifera have the property to be easily absorbed by water-soluble cells, so only small doses are needed to be used as anti-cancer ingredients. This research aims to prove the ability of M. oleifera nanoparticle extract against oral cancer through the expression of tumour necrosis factor α (TNF-α), heat shock protein (HSP27), and interleukin 10 (IL-10). Rat as non-human experimental subjects were divided into four groups: control group (K), treatment group 1 (P1), treatment group 2 (P2), and treatment group 3 (P3). Cancer induction was carried out by injecting with benzo[a]pyrene, and then M. oleifera nanoparticle extract was administered in three forms of treatment doses of 125 μg/mL (P1), 250 μg/mL (P2), and 500 μg/mL (P3). Immunohistochemical examination was analysed through TNF-α, HSP27, and IL-10’s expression. The expression of TNF-α and HSP27 between control and treatment groups was significantly different. P2 had the lowest expression of TNF-α and HSP27. The expression of IL-10 between control and treatment groups was also significantly different. P1 had the lowest expression of IL-10. M. oleifera nanoparticle extract can reduce oral cancer progression by decreasing the expression of TNF-α, HSP27, and IL-10.